A new species Lappula botschantzevii (Boraginaceae) from the Northern Africa - Ovczinnikova, Svetlana (Phytotaxa, 2021)
A new species, Lappula botschantzevii, is described from the desert zone of North-Western Africa. The new species belongs to the section Lappula and is close to the species L. patula, from which it differs in a smaller corolla, a scorpioid inflorescence (bilateral flowers) with loosely spaced flowers, a heteromorphic coenobium with two types of eremocarps: A) winged with glochids and a large number of spines along the edges of the disc of eremocarps and B) with a second short row of spines. The species is described based on samples from collections housed in three herbaria: Herbarium of the Komarov Botanical Institute RAS, Sankt-Peterburg (LE, Russia) and Muséum National d ‘Histoire Naturelle, Paris (P, France), Université de Montpellier (MPU). It is named after the Russian botanist Viktor Petrovich Botschantzev, who spent many years studying the flora of Africa and who collected samples of the new species. The absence of holotypes required the typification of the names of the studied species Lappula patula, L. capensis and L. eckloniana.